'We Are Here': the politics of memory in narrating China's queer feminist history. Issue 4 (3rd July 2020) - Bao, Hongwei
ABSTRACT: This article examines the politics of narrating feminist and queer histories in contemporary China. Focusing on Zhao Jing and Shi Tou's 2015 film, We Are Here, a documentary made to celebrate the twentieth anniversary of the Fourth United Nations World Conference on Women, I examine how the film represents queer women's history in China and in what discourses such a representation is situated. Icontend that the processes of remembrance and forgetting are intertwined in narrating queer women's history in China. Indeed, while the film successfully recovers a hidden queer history, it also risks erasing the history of socialist and Marxist feminism, as well as China's socialist legacies at large. Isuggest that we should think about Chinese feminist and queer movements in terms of continuities and ruptures by paying attention to their articulations to different transnational discourses at specific historical conjunctures. While We Are Here convincingly addresses the transnational influence from liberal feminism, it is also necessary to call attention to the legacies of socialist and Marxist feminism in China and transnationally in contemporary feminist and queer historiography and mediated memories.